Blowback for Renewables – Spatial Reorientation of Wind-, Solar- and Bioenergy Against the Backdrop of Declining Acceptance and Increasing Conflicts of Usage of Acreage in the Rural Zone - Bosch, Stephan; Peyke, Gerd (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
The forced expansion of renewable energy sources has induced within a few years time a cultural landscape of a new kind. The traditional natural scenery, dominated by agricultural parcels, islands of forest, and condensed areas of settlement, is continually being amended by decentralized power plants such as wind parks, solar and biomass power plants. Still we are far from the development of pure energy landscapes, as it is feared by local historic associations and nature conservation organisations. Restrictive regional planning, annual amendments to the principles of remuneration given in the Renewable Energies Act, as well as declining government aid are putting hard spatial strain on the renewable energy system. Yet pressure on the usage of rural space has been augmented by the present development and has led to new dimensions of competition for the usage of acreage. Thus, a discussion of the future role of rural areas as a location for new technologies seems appropriate.